Effective utilization of an Unused Bandwidth in IEEE 802.16 network - Abubakar Ibrahim, Adamu; Salsabil, Sanjir Inam; Lawal, Ibrahim A. (UTEM, 2022)
A large percentage of available bandwidth in IEEE 802.16 networks can be utilised by using previous unused bandwidth. This is a common problem that occurs inside IEEE 802.16 networks, and it manifests itself when a subscriber station in an IEEE 802.16 network's Quality of Service (QOS) assured services is unable to predict how much data is being held back as unused bandwidth. As a direct consequence of this fact, the ongoing research has proposed simulating the process by which the remainder of the reserved bandwidth that is not being used will be recycled in order to enhance the Quality of Service and preserve the existing bandwidth reservation. Therefore, it was conceived that bandwidth might be reserved in the subscriber station separately from the bandwidth that is used for the downlink and the uplink of data transmission. This would prevent wasting the bandwidth. Through the utilization of an appropriate scheduling strategy associated with Round Robin, a simulation of an allocation of unoccupied bandwidth was carried out. The simulation findings reveal that an optimised bandwidth can ensure that the model can recycle 50–60 percent of the average amount of idle bandwidth. This is achieved through the allocation of unused bandwidth scheduling techniques. The findings of this research have demonstrated that it is possible to estimate the amount of data that is set aside as unused bandwidth and reuse it.